The Effect Combining Snakehead Fish Extract, Meniran, and Temulawak on Glycemic Status and Pancreatic Histopathology in High-Fat Diet Diabetic Rats - OK Yulizal; Wa Amalia Zahiah; Erwin Sopacua (Eduvest - Journal of Universal Studies, 2024)
Diabetes mellitus is a metabolic disorder characterized by hyperglycemia, frequently associated with obesity, dyslipidemia, hypertension, and cardiovascular complications, particularly in type 2 diabetes mellitus (DM). In Indonesia, traditional medicine is often favored for its safety and cost-effectiveness compared to synthetic drugs. This study involved 25 male Wistar rats, which were divided into five groups: a control group, an alloxan and high-fat diet group, a pioglitazone group, a plant extract group, and a combination group. Obesity was induced over 27 days through a high-fat diet, followed by the administration of alloxan to elevate blood glucose levels. Glucose measurements were taken at specified intervals, with HbA1c assessed on day 26, and pancreatic histopathology was analyzed post-study. The Kruskal-Wallis test revealed significant differences in weight gain (p = 0.016) and blood glucose levels (p = 0.003) among the groups. Although no significant difference was observed in blood glucose reduction (p = 0.05), the combination group exhibited the most substantial decrease. One-way ANOVA results demonstrated that the combination of the extract and pioglitazone significantly reduced HbA1c levels (p < 0.001), with the second group showing the highest levels and the fourth group displaying the most pronounced reduction. Histopathological analysis indicated damage to the islets of Langerhans in both the pioglitazone and extract groups. The combination of snakehead fish extract, meniran, temulawak, and pioglitazone effectively lowers blood glucose and HbA1c levels; however, it does not appear to ameliorate islet damage, likely due to oxidative stress resulting from the treatments